Komposisi Makanan dan Strategi Makan Ikan Famili Gobiidae di Teluk Pabean, Indramayu - Aldi Chandra Khoncara; . Sulistiono; Charles Parningotan Haratua Simanjuntak; Muhammad Fadjar Rahardjo; Ahmad Zahid (Jurnal Ilmu Pertanian Indonesia, 2018)
The objectives of this study were to identify and evaluate diet composition and feeding strategy of Gobiid fishes in Pabean Bay, Indramayu. Fishes were collected monthly using gill nets, shrimp nets and fixed trap nets from April 2016-March 2017. Diet composition and feeding strategy were analyzed by IRI (Index of Relative Importance) and modification of the graphical Costello method, respectively. Nine species of Gobiidae were captured during the study period, namely Acentrogobius caninus (with total body length range 46-115 mm), Acentrogobius cyanomos (49-108 mm), Boleophthalmus boddarti (95-189 mm), Glossogobius aureus (70-210 mm), Oxyurichthys tentacularis (88-130 mm), Parapocryptes serperaster (112-198 mm), Paratrypauchen microcephalus (100-150 mm), Pseudapocryptes elongatus (88-190 mm), and Taenioides cirratus (160 mm). According to the diet analysis, A. caninus, A. cyanomos, and G. aureus were grouped into crustacivore, while the B. boddarti, P. serperaster, P. microcephalus, and P. elongatus were categorized as phytobenthic feeder. A. caninus, G. aureus, and A. cyanomos exhibited a specialist feeding strategy with the main food was Metapenaeus sp., Metapenaeus sp. and Acetes sp., respectively. B. boddarti, P. serperaster, P. microcephalus, P. elongates displayed a generalized feeding strategy. This research showed that Gobiid fishes occupy different trophic levels and play an important ecological role in Pabean Bay.